EFFECT OF THE ADDITION OF COOKING OIL MANGOSTEEN SKIN AGAINST PEROXIDE LEVELS NUMBERS - Pauzi, Iswari; Anam, Haerul; Dewi, Ni Made Uci Pramesthy (Jurnal Analis Medika Biosains (JAMBS), 2014)
AbstractCooking oil can not be separated from everyday life . Cooking oil is used as a medium heat in a frying process . Helpful addition to cooking oil can be one of the factors that cause disease . Cooking oil used in frying process repeatedly, will oxidize and will form free radicals . Damage due to oil oxidation process was measured with peroxide . Oil damage can be prevented by adding antioxidants.Besides mangosteen fruit contains vitamins and minerals also contain antioxidants found in the skin.The purpose of this study was to determine whether there is the effect of adding mangosteen peel the waste cooking oil on levels of peroxide . The method used is an experimental method to design experiments RAL . The amount of sample used in 2600 ml cooking oil 240 gr mangosteen peel.The research results are statistically tested using One Way Anova test at 95% confidence level ( α = 0.05 ) indicates that there is the effect of mangosteen peel 5 % , 10 % and 15 % w/v significantly to the peroxide concentration on oil cooking.Keywords : Cooking oil , Mangosteen skin